Vibration and noise attenuation performance of compounded periodic struts for helicopter gearbox system. (13th October 2019) - Wang, Fengjiao; Lu, Yang; Lee, Heow Pueh; Ma, Xunjun
Abstract: To reduce the helicopter cabin noise generated from a gearbox, a novel compounded periodic strut is designed with periodic structures connected in series/parallel in the axial direction. In this paper, the emphasis is placed on exploring the vibration transfer performance of the strut in both the axial and lateral directions, along with its attenuation effects on fuselage vibration and cabin noise. First, considering all directions, a complete dynamic model of the designed strut is established based on the spectral finite element method and the transfer matrix method and is extended to the model of the gearbox/struts system. Based on this model, simulation predictions indicate that the designed strut exhibits better broadband vibration attenuation in the lateral directions compared to that in the axial direction. Under this combined action, the translational vibration transmitted to the fuselage floor can be effectively isolated. The maximum acceleration attenuation can be more than 40 dB. These conclusions are verified by further experimental studies, which confirm that the numerical model can accurately predict the strut's vibration control results in the helicopter model. Subsequently, the noise transfer performance from the gearbox to the cabin noise field is experimentally studied using the helicopter model. Similar to the vibration control results, satisfactory broadband noise attenuation is obtained when using the designed compounded periodic strut. Among the frequencies of the stop bands, the maximum noise attenuation is more than 30 dB.